Dehydrogenation of dodecahydro-N-ethylcarbazole on Pt(111) - Gleichweit, Christoph; Amende, Maximilian; Schernich, Stefan; Zhao, Wei; Lorenz, Michael Peter Andreas; Höfert, Oliver; Brückner, Nicole; Wasserscheid, Peter; Libuda, Jörg; Steinrück, Hans-Peter; Papp, Christian (Chemsuschem, 2013)
Sloshing hydrogen: Liquid organic hydrogen carriers are high-boiling organic molecules, which can be reversibly hydrogenated and dehydrogenated in catalytic processes and are, therefore, a promising chemical hydrogen storage material. One of the promising candidates is the pair N-ethylcarbazole/perhydro- N-ethylcarbazole (NEC/H-NEC). The dehydrogenation and possible side reactions on a Pt(111) surface are evaluated in unprecedented detail. Copyright © 2013 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.

Environmental and health impact assessment of Liquid Organic Hydrogen Carrier (LOHC) systems - challenges and preliminary results - Markiewicz, M.; Zhang, Y. Q.; Bösmann, Andreas; Brückner, Nicole; Thöming, J.; Wasserscheid, Peter; Stolte, S. (Energy and Environmental Science, 2015)
Liquid Organic Hydrogen Carrier (LOHC) systems offer a very attractive way to store and transport hydrogen, a technical feature that is highly desirable to link unsteady energy production from renewables with the vision of a sustainable, CO2-free, hydrogen-based energy system. LOHCs can be charged and discharged with considerable amounts of hydrogen in cyclic, catalytic hydrogenation and dehydrogenation processes. As their physico-chemical properties are very similar to diesel, today's infrastructure for liquid fuels can be used for their handling thus greatly facilitating the step-wise transition from today's fossil system to a CO2 emission free energy supply for both, stationary and mobile applications. However, for a broader application of these liquids it is mandatory to study in addition to their technical performance also their potential impact on the environment and human health. This paper presents the first account on the toxicological profile of some potential LOHC structures. Moreover, it documents the importance of an early integration of hazard assessment in technology development and reveals for the specific case of LOHC structures the need for additional research in order to overcome some challenges in the hazard assessment for these liquids.

Evaluation of Industrially Applied Heat-Transfer Fluids as Liquid Organic Hydrogen Carrier Systems - Brückner, Nicole; Obesser, Katharina; Bösmann, Andreas; Teichmann, Daniel; Arlt, Wolfgang; Dungs, Jennifer; Wasserscheid, Peter (Chemsuschem, 2014)
Liquid organic hydrogen carrier (LOHC) systems offer a very attractive method for the decentralized storage of renewable excess energy. In this contribution, industrially well-established heat-transfer oils (typically sold under trade names, e.g., Marlotherm) are proposed as a new class of LOHC systems. It is demonstrated that the liquid mixture of isomeric dibenzyltoluenes (m.p. -39° to -34°C, b.p. 390°C) can be readily hydrogenated to the corresponding mixture of perhydrogenated angenated to the corresponding mixture of perhydrogenated an-alogues by binding 6.2 wt% of H2. The liquid H2 -rich form can be stored and transported similarly to diesel fuel. It readily undergoes catalytic dehydrogenation at temperatures above 260°C, which proves its applicability as a reversible H2 carrier. The presented LOHC systems are further characterized by their excellent technical availability at comparably low prices, full registration of the H2-lean forms, and excellent thermal stabilities.

Surface Reactions of Dicyclohexylmethane on Pt(111) - Gleichweit, Christoph; Amende, Maximilian; Höfert, Oliver; Xu, Tao; Späth, Florian; Brückner, Nicole; Wasserscheid, Peter; Libuda, Jörg; Steinrück, Hans-Peter; Papp, Christian (Journal of Physical Chemistry C, 2015)
We investigated the surface reaction of the liquid organic hydrogen carrier dicydohexylmethane (DCHM) on Pt(111) in ultrahigh vacuum by high-resolution X-ray photoelectron spectroscopy, temperature-programmed desorption, near-edge X-ray absorption fine structure, and infrared reflection absorption spectroscopy. Additionally, the hydrogen-lean molecule diphenylmethane and the relevant molecular fragments of DCHM, methylcyclohexane, and toluene were studied to elucidate the reaction steps of DCHM. We find dehydrogenation of DCHM in the range of 200-260 K, to form a double-sided pi-allylic species coadsorbed with hydrogen. Subsequently, similar to 30% of the molecules desorb, and for similar to 70%, one of the pi-allyls reacts to a phenyl group between 260 and 330 K, accompanied by associative hydrogen desorption. Above 360 K, the second pi-allylic species is dehydrogenated to a phenyl ring. This is accompanied by C-H bond scission at the methylene group, which is an unwanted decomposition step in the hydrogen storage cycle, as it alters the original hydrogen carrier DCHM. Above 450 K, we find further decomposition steps which we assign to C-H abstraction at the phenyl rings.